Full-concentration gradient layered oxide positive electrode material and preparation method and application thereof
By preparing the full-concentration gradient layered oxide positive electrode material, the problems of low reversible capacity and poor circulation performance of sodium ion battery materials are solved, and high capacity retention and stable circulation performance are achieved.
Patent Information
- Application Number
- CN202411819723.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-21
AI Technical Summary
The reversible capacity of the positive electrode material of sodium ion battery is low and the circulation performance is poor, especially the high-nickel layered oxide materials have problems in thermal stability, air stability and circulation performance.
A full concentration gradient layered oxide positive electrode material is used. The preparation method includes mixing a nickel-lean iron solution with a nickel-rich iron solution, and performing a feed reaction in a reactor, adding a complexing agent and an antioxidant, and mixing the calcining precursor with a sodium salt to obtain the material. From the core to the surface layer, the relative content of nickel and iron elements continues to decrease, and the relative content of manganese elements continues to increase, constructing the full radial concentration gradient change of each transition metal element.
The reversible capacity and cycling performance of the positive electrode material of sodium ion battery were improved, which was specifically manifested as the initial reversible capacity reached 137.5mAh/g, the capacity retention rate after 100 cycles was as high as 92.4%, and the transition metal ion dissolution amount was significantly reduced, enhancing the surface stability of the material.
Smart Images

Figure CN119660830A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery electrode materials, and in particular relates to a full concentration gradient layered oxide positive electrode material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have the advantages of high abundance of working elements, low cost, long cycle life, and good safety performance, and have gradually attracted the attention of many scholars. However, this type of battery has a significant problem of low energy density, and the positive electrode materials of sodium-ion batteries need to further improve their specific capacity. Today's successful commercial sodium positive electrode materials mainly include phosphates and low-nickel layered oxides: sodium vanadium phosphate has the characteristics of high safety and long cycle life, but poor conductivity and low actual specific capacity of only 120mAh / g, while the reversible specific capacity of low-nickel layered oxides is slightly higher than that of phosphates, but it still cannot meet the high requirements of power batteries for energy density.
[0003] A large number of studies have shown that by appropriately increasing the nickel content in layered oxide materials, the specific capacity of the material can be effectively increased (about 140 mAh / g), thereby increasing the energy density of sodium-ion batteries. However, although increasing the nickel content in such materials can increase their actual reversible capacity, it will also cause thermal stability, air stability and cycle performance to deteriorate. The reason is that, firstly, due to the increase in nickel content, the thermal decomposition temperature decreases and the heat release increases, which means that the thermal stability of the material deteriorates. The Na released from high-nickel materials at the same potential is + More than low nickel content materials, and Ni 4+ High content is easy to reduce to Ni 3+ In order to maintain charge balance, the material will release oxygen, making it less stable. Secondly, high nickel materials can easily react with H2O and CO2 in the air to produce NaOH and Na2CO3, which makes battery processing more difficult and causes the electrochemical performance of the material to deteriorate. In addition, under high sodium removal conditions, Ni 4+ The high oxidation activity can cause serious side reactions at the material / electrolyte interface, consuming carbonate solvents to decompose the system and produce gas; at the same time, the Fe 3+ It can be further oxidized to Fe in the side reaction involving the electrolyte. 4+ , thereby inducing an irreversible phase change on the surface of the material through the Jiang-Taylor distortion, which increases the material capacity decay during the battery cycle and poses a greater safety hazard. Therefore, reducing the surface nickel-iron content helps to improve the working stability of this type of material and the corresponding battery pack. In summary, while increasing the nickel content of the layered oxide material, its surface and interface stability should be improved to achieve an improvement in its comprehensive electrochemical performance.
[0004] In order to improve the surface and interfacial stability of this type of sodium-based positive electrode materials, scholars in the industry have conducted relevant explorations. For example, Chinese patent CN116826014A discloses a coated sodium-based layered oxide composite material, its preparation method and sodium-ion battery, the composite material includes a substrate and a coating layer coated on the surface of the substrate; the substrate is an O3-type sodium-based layered transition metal oxide, and the coating layer is a lithium cobalt oxide layer. The invention generates a dense lithium cobalt oxide protective layer on the surface of the substrate, so that the substrate cannot directly contact the air, reduces the side reaction of the residual alkali on the surface of the substrate and the air, and improves the air stability of the material; at the same time, the coating layer also improves the conductivity of the substrate, and prevents direct contact between the electrolyte and the substrate, reduces the side reaction of the interface of the substrate material, and then improves the cyclability of the material, and obtains a sodium-based positive electrode material with strong air stability and excellent electrochemical properties. For example, Chinese patent CN117276551A discloses a NaMPO4 or NaM 1 / 2 SO3 coated NaFe x Mn y O2 positive electrode material, M is a divalent metal ion, it has a uniform coating layer, a stable material structure, almost no impurity phase, and has better cycle performance. x Mn y The surface of O2 positive electrode material is not conducive to the formation of residual alkali with Na + The coating of the channel avoids direct contact with the air, further improving the air stability of the material and optimizing the performance of the material. However, the use of surface coating materials can improve the cyclic stability of the material, but a large number of studies have found that the junction between the coating and the body of the material is prone to separation during long cycles. For heterogeneous materials with this type of core-shell structure, there are differences in the volume changes of the heterogeneous structure, that is, different degrees of volume contraction and expansion during long-term charge and discharge cycles will lead to heterogeneous separation, so that the long-term cycle performance of this type of material cannot be effectively improved, and therefore the continued effectiveness of this type of coated core-shell structure during repeated charge and discharge of the material cannot be guaranteed.
[0005] In addition, Chinese patent CN115020676A discloses a sodium ion battery positive electrode material with stable oxygen valence and a preparation method thereof, in which a manganese, nickel and iron concentration gradient metal element is added as a core material by a coprecipitation method, and a coating layer is provided on its outer layer. The positive electrode material prepared in this patent does not have independent spherical secondary particles, but is only an agglomeration stack of small particles with a particle size of 100nm. Since the particles are small and the specific surface area of the material is large, the side reaction with the electrolyte will be more serious in a long cycle. It can be seen that the capacity retention rate after 100 cycles at a current density of 0.5C is only 80.20%, so the cycle life of small particle materials is short and it is difficult to apply stably. Summary of the invention
[0006] In response to the technical problems of low reversible capacity and poor cycle performance of sodium-ion batteries, a full-concentration gradient layered oxide positive electrode material and its preparation method and application are proposed.
[0007] To achieve the above object, the technical solution of the present invention is implemented as follows:
[0008] A method for preparing a full concentration gradient layered oxide positive electrode material, the steps are as follows:
[0009] (1) adding poor nickel-iron solution B to a storage tank containing rich nickel-iron solution A at a speed u1, and mixing in real time in the storage tank to obtain solution C; at the same time, adding solution C to a reactor containing a mixed solution of a complexing agent and an antioxidant at a speed u2; and the complexing agent solution is simultaneously introduced into the reactor with an alkaline solution at 15-35 mL / h to perform a feeding reaction;
[0010] (2) During the reaction process of feeding, an inert gas is introduced, and when the solution C is completely fed, the feeding of the complexing agent solution and the alkali solution is stopped; the stirring speed in the kettle is adjusted and the reaction mixture is aged at a constant temperature, and the precursor is obtained after separation, washing and drying;
[0011] (3) The precursor is mixed with sodium salt and then calcined to obtain a full concentration gradient layered oxide positive electrode material.
[0012] In the above step (1), the mass ratio of the complexing agent to the antioxidant in the mixed solution of the complexing agent and the antioxidant is (1-3):(1-5), the concentration of the complexing agent in the mixed solution is 10-30 g / L; the concentration of the complexing agent solution is 80-130 g / L; and the concentration of the alkaline solution is 4-10 mol / L.
[0013] Furthermore, a mixed solution of a complexing agent and an antioxidant in an amount of 25-35% of the reactor volume is added into the reactor.
[0014] The complexing agent is any one of ammonia water, ammonium sulfate, ethylenediamine and ammonium citrate; the antioxidant is sodium ascorbate or ascorbic acid; and the alkaline solution is a mixture of one or more of sodium hydroxide and potassium hydroxide solutions.
[0015] Three transition metal salts, nickel salt, iron salt and manganese salt, are used to prepare nickel-rich iron salt solution A and nickel-poor iron salt solution B with a total transition metal ion concentration of 1-2.5 mol / L. The nickel salt is one of nickel sulfate, nickel nitrate and nickel chloride, the iron salt is one of ferrous sulfate, ferrous nitrate and ferrous chloride, and the manganese salt is one of manganese sulfate, manganese nitrate and manganese chloride.
[0016] The molar ratio of nickel, iron and manganese ions in the nickel-rich iron solution A is Ni:Fe:Mn=(0.40-0.60):(0.25-0.40):(0-0.25); the molar ratio of nickel, iron and manganese ions in the nickel-poor iron solution B is Ni:Fe:Mn=(0.00-0.30):(0.00-0.20):(0.60-1.00).
[0017] Above u1=15-25mL / h, u2=45-75mL / h, and u2=3u1.
[0018] During the above-mentioned feeding reaction process, the inert gas is nitrogen or argon; the temperature in the kettle is 45-60°C, PH=10.5-12.0, the stirring speed in the kettle is 600-1000r / min; and the constant temperature aging time is 8-12h.
[0019] In the above step (3), the molar ratio of the precursor to the sodium element in the sodium salt is 1:(1.01-1.05).
[0020] Furthermore, the sodium salt is sodium carbonate, sodium nitrate or sodium hydroxide.
[0021] The calcination in the above step (3) refers to heating to 900-1000°C at 3°C / min and maintaining the temperature for 12-20h.
[0022] The full concentration gradient layered oxide positive electrode material prepared by the above preparation method has a relative content of nickel and iron elements decreasing from the core to the surface, and a relative content of manganese element increasing.
[0023] The total Ni content of the material is high, which makes it have a higher reversible capacity, and Fe can be + The charge balance is maintained by changing the valence during the embedding and de-embedding process. In addition, the concentration gradient change in the radial direction of the secondary particles of the material significantly reduces the Ni and Fe content on the surface of the material compared with the overall average value, reducing the unstable high-valence transition metal ions (Ni 4+ with Fe 3 + etc.) relative content, among which Fe 3+ It can be further converted into Fe that is prone to Jahn-Taylor distortion in the interfacial side reaction involving the electrolyte solution. 4+ In this type of layered oxide material, if Fe is to migrate from the octahedral position of the transition metal layer to the interstitial position of the tetrahedral position of the uranium layer, the unit cell energy needs to increase by at least 0.7eV. When multiple Fe atoms form clusters, the energy required for this migration decreases significantly. For example, the migration barrier of a cluster formed by three Fe atoms will be reduced to 0.2eV. This is because when Fe with the Jean-Taylor distortion effect 4+After agglomeration, the transition metal layer Fe can adapt to the shortening of the Fe-O bonds of the surrounding Fe. This effect can significantly reduce the energy of the tetrahedral position (metastable, higher energy) of the uranium layer, thereby greatly increasing the probability of Fe migration. Therefore, reducing the content of Fe in the surface layer can reduce Fe 4+ The formation and subsequent cluster migration of the material can inhibit the ion mixing and dissolution on the surface of the material, delay the irreversible phase change of the material and electrolyte contamination, and improve the cycle performance of the sodium ion battery.
[0024] The material is spherical or quasi-spherical, and its overall composition is NaNi x Fe y Mn z O2, wherein 0.33≤x≤0.50, 0.20≤y≤0.33, 0.2≤z≤0.4, and x+y+z=1.
[0025] Application of the above-mentioned full concentration gradient layered oxide positive electrode material in sodium ion batteries.
[0026] The beneficial effects produced by the present invention are:
[0027] The material prepared by the present invention has a relatively low relative content of Ni and Fe from the core to the surface, and a relatively high content of Mn from the core to the surface, thereby constructing a full radial concentration gradient change of each transition metal element from the core to the surface. The material has a high total Ni content, which makes it have a high reversible capacity. At the same time, Fe can be + The charge balance is maintained by changing the valence during the insertion and removal process. In addition, the concentration gradient change in the radial direction of the secondary particles of the material significantly reduces the Ni and Fe content on the surface of the material compared with the overall average value, reducing the unstable high-valent transition metal ions (Ni 4+ with Fe 3+ etc.) relative content, among which Fe 3+ It can be further converted into Fe that is prone to Jahn-Taylor distortion in the interfacial side reaction involving the electrolyte solution. 4+ In this type of layered oxide material, if Fe is to migrate from the octahedral position of the transition metal layer to the interstitial position of the tetrahedral position of the uranium layer, the unit cell energy needs to increase by at least 0.7eV. When multiple Fe atoms form clusters, the energy required for this migration decreases significantly. For example, the migration barrier of a cluster formed by three Fe atoms will be reduced to 0.2eV. This is because when Fe with the Jean-Taylor distortion effect 4+ After agglomeration, the transition metal layer Fe can adapt to the shortening of the Fe-O bonds of the surrounding Fe. This effect can significantly reduce the energy of the tetrahedral position (metastable, higher energy) of the uranium layer, thereby greatly increasing the probability of Fe migration. Therefore, reducing the content of Fe in the surface layer can reduce Fe 4+The formation and subsequent cluster migration of the material inhibit the mixing and dissolution of ions on the surface of the material, delay the irreversible phase change of the material and the contamination of the electrolyte, and improve the cycle performance of the sodium ion battery. Specifically, the initial reversible capacity of the sodium ion battery positive electrode material prepared by the present invention reaches 137.5mAh / g at 0.1C, and the capacity retention rate can be as high as 92.4% after 100 cycles at a current density of 1.0C. In addition, the transition metal ion dissolution determination of the material after the cycle found that the total dissolution amount of the optimal material was only 5.31ppm. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 This is the SEM image of the full concentration gradient layered oxide material obtained in Example 1.
[0030] Figure 2 The cross-sectional SEM image and EDS line scan image of relative element content of the full concentration gradient layered oxide material obtained in Example 1 are shown.
[0031] Figure 3 This is the XRD diffraction pattern of the full concentration gradient oxide layered material obtained in Example 1. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] The preparation method of the full concentration gradient layered oxide positive electrode material of this embodiment comprises the following steps:
[0035] Step 1: With nickel sulfate, ferrous sulfate and manganese sulfate as transition metal salts, prepare 1L nickel-rich iron salt solution A (Ni:Fe:Mn=0.50:0.25:0.25) and 500mL nickel-poor iron salt solution B (Ni:Fe:Mn=0.20:0.10:0.70) with a total transition metal ion concentration of 2.0mol / L, and prepare 8mol / L sodium hydroxide solution, a mixed solution of 20g / L ammonia water and 50g / L sodium ascorbate, and 102g / L ammonia solution.
[0036] Step 2: First, add a mixed solution of ammonia water and sodium ascorbate in step 1 to a 5L reactor with a volume of 30%. The nickel-poor iron solution B is added to the storage tank containing the nickel-rich iron solution A at a speed of 20mL / h, and a stirring device is set in the storage tank for real-time mixing to obtain solution C; while the nickel-poor iron solution B is added to the storage tank, solution C is passed into the reactor at a speed of 60mL / h, ammonia solution at a speed of 30mL / h, and sodium hydroxide solution is passed into the reactor at a self-controlled flow rate of the reactor to carry out real-time feeding reaction. During the feeding reaction, nitrogen is introduced for gas protection, the temperature in the kettle is controlled to be 50°C, PH=10.80, and the stirring speed in the kettle is 800r / min. After the feeding reaction is completed, the stirring speed in the kettle is modulated to 300r / min, and the temperature is kept constant for 10h. Then filter for solid-liquid separation, wash with deionized water 3 times, and place the solid part at 100°C for constant temperature drying for 10h to obtain a full concentration gradient layered material precursor.
[0037] Step 3: The precursor obtained in step 2 is uniformly mixed with sodium carbonate and then calcined, wherein the molar ratio of the precursor to the sodium element is 1:1.03, and the calcination procedure is: heating to 950°C at 3°C / min and maintaining the constant temperature for 20h, and finally cooling to room temperature at 3°C / min to obtain the full concentration gradient layered oxide material (the overall composition is NaNi 0.4 Fe 0.2 Mn 0.4 O2).
[0038] Figure 1 This is a SEM image of the full concentration gradient layered oxide material obtained in Example 1. As can be seen from the figure, the material is a secondary particle formed by primary particles, the primary particle size is about 0.8um, the secondary particle size is about 6um, and the texture is compact and the sphericity is good.
[0039] Figure 2The cross-sectional SEM image and EDS element relative content line scan image of the full concentration gradient layered oxide material obtained in Example 1. It can be seen from the figure that the relative contents of Ni, Fe, and Mn in the radial direction of the secondary particles of the material gradually change from 47.4%, 22.2%, and 30.4% in the core to 38.3%, 11.1%, and 50.6% in the surface layer, and the high Ni and Fe core and low Ni and Fe surface layer are constructed by the concentration gradient change of each element.
[0040] Figure 3 This is the XRD diffraction pattern of the full concentration gradient oxide layered material obtained in Example 1. As can be seen from the figure, each crystal plane has clear peaks with high peak intensity, among which the 003 and 104 peaks are clearly visible, proving that the material has a good layered structure of the R-3m space group.
[0041] Example 2
[0042] The preparation method of the full concentration gradient layered oxide positive electrode material of this embodiment comprises the following steps:
[0043] Step 1: With nickel sulfate, ferrous sulfate and manganese sulfate as metal salts, prepare 1L nickel-rich iron salt solution A (Ni:Fe:Mn=0.60:0.30:0.10) with a total metal ion concentration of 2.0mol / L and 500mL nickel-poor iron salt solution B (Ni:Fe:Mn=0.00:0.00:1.00), 8mol / L sodium hydroxide solution, a mixed solution of 25g / L ammonia water and 40g / L sodium ascorbate, and 102g / L ammonia solution.
[0044] Step 2: First, add a mixed solution of ammonia water and sodium ascorbate in step 1 to a 5L reactor with a volume of 30%. The nickel-poor iron solution B is added to the storage tank containing the nickel-rich iron solution A at a speed of 15mL / h, and a stirring device is set in the storage tank for real-time mixing to obtain solution C; while the nickel-poor iron solution B is added to the storage tank, solution C is passed into the reactor at a speed of 45mL / h, ammonia solution at a speed of 35mL / h, and sodium hydroxide solution is passed into the reactor at a self-controlled flow rate of the reactor to carry out real-time feeding reaction. During the feeding reaction, nitrogen is introduced for gas protection, the temperature in the kettle is controlled to be 55°C, PH=11.2, and the stirring speed in the kettle is 900r / min. After the feeding reaction is completed, the stirring speed in the kettle is modulated to 200r / min, and the temperature is kept constant for 8h. Then filter for solid-liquid separation, wash with deionized water 3 times, and place the solid part at 100°C for constant temperature drying for 10h to obtain a full concentration gradient layered material precursor.
[0045] Step 3: The precursor obtained in step 2 is uniformly mixed with sodium carbonate and then calcined, wherein the molar ratio of the precursor to the sodium element is 1:1.03, and the calcination procedure is: heating to 900°C at 3°C / min and maintaining the constant temperature for 18h, and finally cooling to room temperature at 3°C / min to obtain the full concentration gradient layered oxide material (the overall composition is NaNi 0.4 Fe 0.2 Mn 0.4 O2).
[0046] Example 3
[0047] The preparation method of the full concentration gradient layered oxide positive electrode material of this embodiment comprises the following steps:
[0048] Step 1: With nickel sulfate, ferrous sulfate and manganese sulfate as metal salts, prepare 1L nickel-rich iron salt solution A (Ni:Fe:Mn=0.40:0.40:0.20) and 500mL nickel-poor iron salt solution B (Ni:Fe:Mn=0.20:0.20:0.60) with a total metal ion concentration of 2.0mol / L, and prepare 8mol / L sodium hydroxide solution, a mixed solution of 25g / L ammonia water and 40g / L sodium ascorbate, and 130g / L ammonia solution.
[0049] Step 2: First, add a mixed solution of ammonia water and sodium ascorbate in step 1 to a 5L reactor with a volume of 35%. The nickel-poor iron solution B is added to the storage tank containing the nickel-rich iron solution A at a speed of 25mL / h, and a stirring device is set in the storage tank for real-time mixing to obtain solution C; while the nickel-poor iron solution B is added to the storage tank, solution C is passed into the reactor at a speed of 75mL / h, ammonia solution at a speed of 35mL / h, and sodium hydroxide solution is passed into the reactor at a reactor self-controlled flow rate to carry out real-time feeding reaction. During the feeding reaction, nitrogen is introduced for gas protection, the temperature in the kettle is controlled to be 45°C, PH=10.5, and the stirring speed in the kettle is 600r / min. After the feeding reaction is completed, the stirring speed in the kettle is modulated to 300r / min, and the constant temperature is aged for 12h. Then filter for solid-liquid separation, wash with deionized water 3 times, and place the solid part at 100°C for 10h to obtain a full concentration gradient layered material precursor.
[0050] Step 3: The precursor obtained in step 2 is uniformly mixed with sodium carbonate and then calcined, wherein the molar ratio of the precursor to the sodium element is 1:1.04, and the calcination procedure is: heating to 950°C at 3°C / min and maintaining the temperature for 15h, and finally cooling to room temperature at 3°C / min to obtain the full concentration gradient layered oxide material (the overall composition is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2).
[0051] Example 4
[0052] The preparation method of the full concentration gradient layered oxide positive electrode material of this embodiment comprises the following steps:
[0053] Step 1: With nickel nitrate, ferrous nitrate and manganese nitrate as metal salts, prepare 1L nickel-rich iron salt solution A (Ni:Fe:Mn=0.40:0.40:0.20) and 500mL nickel-poor iron salt solution B (Ni:Fe:Mn=0.20:0.20:0.60) with a total metal ion concentration of 2.0mol / L, prepare 4mol / L sodium hydroxide solution, a mixed solution of 10g / L ammonia water and 45g / L sodium ascorbate, and 95g / L ammonia solution.
[0054] Step 2: First, add a mixed solution of ammonia water and sodium ascorbate in step 1 to a 5L reactor with a volume of 30%. The nickel-poor iron solution B is added to the storage tank containing the nickel-rich iron solution A at a speed of 20mL / h, and a stirring device is set in the storage tank for real-time mixing to obtain solution C; while the nickel-poor iron solution B is added to the storage tank, solution C is passed into the reactor at a speed of 60mL / h, ammonia solution at a speed of 20mL / h, and sodium hydroxide solution is passed into the reactor at a self-controlled flow rate of the reactor to carry out real-time feeding reaction. During the feeding reaction, nitrogen is introduced for gas protection, the temperature in the kettle is controlled to be 52°C, PH=10.8, and the stirring speed in the kettle is 700r / min. After the feeding reaction is completed, the stirring speed in the kettle is modulated to 200r / min, and the temperature is kept constant for 8h. Then filter for solid-liquid separation, wash with deionized water 3 times, and place the solid part at 100°C for constant temperature drying for 10h to obtain a full concentration gradient layered material precursor.
[0055] Step 3: The precursor obtained in step 2 is uniformly mixed with sodium carbonate and then calcined, wherein the molar ratio of the precursor to the sodium element is 1:1.02, and the calcination procedure is: heating to 900°C at 3°C / min and maintaining the constant temperature for 12h, and finally cooling to room temperature at 3°C / min to obtain the full concentration gradient layered oxide material (the overall composition is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2).
[0056] Example 5
[0057] The preparation method of the full concentration gradient layered oxide positive electrode material of this embodiment comprises the following steps:
[0058] Step 1: With nickel nitrate, ferrous nitrate and manganese nitrate as metal salts, prepare 1L nickel-rich iron salt solution A (Ni:Fe:Mn=0.60:0.30:0.00) and 500mL nickel-poor iron salt solution B (Ni:Fe:Mn=0.30:0.00:1.00) with a total metal ion concentration of 2.5mol / L, and prepare 10mol / L sodium hydroxide solution, a mixed solution of 30g / L ammonia water and 30g / L sodium ascorbate, and 80g / L ammonia solution.
[0059] Step 2: First, add a mixed solution of ammonia water and sodium ascorbate in step 1 to a 5L reactor with a volume of 25%. The nickel-poor iron solution B is added to the storage tank containing the nickel-rich iron solution A at a speed of 20mL / h, and a stirring device is set in the storage tank for real-time mixing to obtain solution C; while the nickel-poor iron solution B is added to the storage tank, solution C is passed into the reactor at a speed of 60mL / h, ammonia solution at a speed of 15mL / h, and sodium hydroxide solution is passed into the reactor at a reactor self-controlled flow rate to carry out real-time feeding reaction. During the feeding reaction, nitrogen is introduced for gas protection, the temperature in the kettle is controlled to be 60°C, PH=12, and the stirring speed in the kettle is 1000r / min. After the feeding reaction is completed, the stirring speed in the kettle is modulated to 150r / min, and the constant temperature is aged for 12h. Then filter for solid-liquid separation, wash with deionized water 3 times, and place the solid part at 100°C for 10h to obtain a full concentration gradient layered material precursor.
[0060] Step 3: The precursor obtained in step 2 is uniformly mixed with sodium carbonate and then calcined, wherein the molar ratio of the precursor to the sodium element is 1:1.05, and the calcination procedure is: heating to 1000°C at 3°C / min and maintaining the constant temperature for 12h, and finally cooling to room temperature at 3°C / min to obtain the full concentration gradient layered oxide material (the overall composition is NaNi 0.5 Fe 0.3 Mn 0.2 O2).
[0061] Comparative Example 1
[0062] The preparation method of the full concentration gradient layered oxide positive electrode material of this comparative example is different from that of Example 1 in that the Fe concentration is always consistent during the feeding process, and the steps are as follows:
[0063] Step 1: With nickel sulfate, ferrous sulfate and manganese sulfate as transition metal salts, prepare 1L nickel-rich iron salt solution A (Ni:Fe:Mn=0.50:0.20:0.25) and 500mL nickel-poor iron salt solution B (Ni:Fe:Mn=0.20:0.20:0.70) with a total transition metal ion concentration of 2.0mol / L, and prepare 8mol / L sodium hydroxide solution, a mixed solution of 20g / L ammonia water and 50g / L sodium ascorbate, and 102g / L ammonia solution.
[0064] Step 2: First, add a mixed solution of ammonia water and sodium ascorbate in step 1 to a 5L reactor with a volume of 30%. The nickel-poor iron solution B is added to the storage tank containing the nickel-rich iron solution A at a speed of 20mL / h, and a stirring device is set in the storage tank for real-time mixing to obtain solution C; while the nickel-poor iron solution B is added to the storage tank, solution C is passed into the reactor at a speed of 60mL / h, ammonia solution at a speed of 30mL / h, and sodium hydroxide solution is passed into the reactor at a self-controlled flow rate of the reactor to carry out real-time feeding reaction. During the feeding reaction, nitrogen is introduced for gas protection, the temperature in the kettle is controlled to be 50°C, PH=10.80, and the stirring speed in the kettle is 800r / min. After the feeding reaction is completed, the stirring speed in the kettle is modulated to 300r / min, and the temperature is kept constant for 10h. Then filter for solid-liquid separation, wash with deionized water 3 times, and place the solid part at 100°C for constant temperature drying for 10h to obtain a full concentration gradient layered material precursor.
[0065] Step 3: The precursor obtained in step 2 is uniformly mixed with sodium carbonate and then calcined, wherein the molar ratio of the precursor to the sodium element is 1:1.03, and the calcination procedure is: heating to 950°C at 3°C / min and maintaining the constant temperature for 20h, and finally cooling to room temperature at 3°C / min to obtain the full concentration gradient layered oxide material (the overall composition is NaNi 0.4 Fe 0.2 Mn 0.4 O2).
[0066] Comparative Example 2
[0067] The preparation method of the full concentration gradient layered oxide positive electrode material of this comparative example comprises the following steps:
[0068] Step 1: With nickel sulfate, ferrous sulfate and manganese sulfate as transition metal salts, prepare 1L nickel-rich iron salt solution A (Ni:Fe:Mn=0.50:0.10:0.25) and 500mL nickel-poor iron salt solution B (Ni:Fe:Mn=0.20:0.40:0.70) with a total transition metal ion concentration of 2.0mol / L, and prepare 8mol / L sodium hydroxide solution, a mixed solution of 20g / L ammonia water and 50g / L sodium ascorbate, and 102g / L ammonia solution.
[0069] Step 2: First, add a mixed solution of ammonia water and sodium ascorbate in step 1 to a 5L reactor with a volume of 30%. The nickel-poor iron solution B is added to the storage tank containing the nickel-rich iron solution A at a speed of 20mL / h, and a stirring device is set in the storage tank for real-time mixing to obtain solution C; while the nickel-poor iron solution B is added to the storage tank, solution C is passed into the reactor at a speed of 60mL / h, ammonia solution at a speed of 30mL / h, and sodium hydroxide solution is passed into the reactor at a self-controlled flow rate of the reactor to carry out real-time feeding reaction. During the feeding reaction, nitrogen is introduced for gas protection, the temperature in the kettle is controlled to be 50°C, PH=10.80, and the stirring speed in the kettle is 800r / min. After the feeding reaction is completed, the stirring speed in the kettle is modulated to 300r / min, and the temperature is kept constant for 10h. Then filter for solid-liquid separation, wash with deionized water 3 times, and place the solid part at 100°C for constant temperature drying for 10h to obtain a full concentration gradient layered material precursor.
[0070] Step 3: The precursor obtained in step 2 is uniformly mixed with sodium carbonate and then calcined, wherein the molar ratio of the precursor to the sodium element is 1:1.03, and the calcination procedure is: heating to 950°C at 3°C / min and maintaining the constant temperature for 20h, and finally cooling to room temperature at 3°C / min to obtain the full concentration gradient layered oxide material (the overall composition is NaNi 0.4 Fe 0.2 Mn 0.4 O2). The Fe in this material presents an inverse gradient to that in Example 1, i.e., more Fe is present on the surface.
[0071] Comparative Example 3
[0072] The preparation method of the layered oxide positive electrode material of this comparative example is different from that of Example 1 in that the core-shell is non-gradient, but Ni and Fe are still more inside and less outside, and the steps are as follows:
[0073] Step 1: With nickel sulfate, ferrous sulfate and manganese sulfate as transition metal salts, prepare nickel-rich iron salt solution A (Ni:Fe:Mn=0.50:0.25:0.25) and nickel-poor iron salt solution B (Ni:Fe:Mn=0.20:0.10:0.70) with a total transition metal ion concentration of 2.0 mol / L, prepare 8 mol / L sodium hydroxide solution, a mixed solution of 20 g / L ammonia water and 50 g / L sodium ascorbate, and 102 g / L ammonia solution.
[0074] Step 2: First, add 30% of the mixed solution of ammonia water and sodium ascorbate in step 1 to a 5L reactor. The nickel-rich iron solution A and the nickel-poor iron salt solution B are introduced into the reactor at a speed of 60mL / h, the ammonia solution at a speed of 30mL / h, and the sodium hydroxide solution at the reactor's self-controlled flow rate to carry out real-time feeding reaction; wherein, solution A (1L) and B (500mL) are fed in sequence, nitrogen is introduced during the reaction process for gas protection, the temperature in the reactor is controlled to be 50°C, PH=10.80, and the stirring speed in the reactor is 800r / min. After the feeding reaction is completed, the stirring speed in the reactor is modulated to 300r / min, and the temperature is kept constant for 10h. Then filter to separate the solid and liquid, wash with deionized water 3 times, and place the solid part at 100°C for 10h to obtain a layered material precursor.
[0075] Step 3: The precursor obtained in step 2 is uniformly mixed with sodium carbonate and then calcined, wherein the molar ratio of the precursor to the sodium element is 1:1.03, and the calcination procedure is: heating to 950°C at 3°C / min and maintaining the constant temperature for 20h, and finally cooling to room temperature at 3°C / min to obtain the layered oxide material (the overall composition is NaNi 0.4 Fe 0.2 Mn 0.4 O2).
[0076] Application Examples
[0077] The positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-3 were respectively applied to sodium ion batteries. The preparation method of the sodium ion batteries is as follows:
[0078] (1) Preparation of positive electrode sheet: The above-obtained full concentration gradient layered oxide material, binder PVDF and conductive agent SP were weighed in a mass ratio of 8:1:1, dissolved in NMP, and stirred to form a slurry of a certain viscosity. The slurry was coated on the current collector copper foil, then dried at 100°C, rolled, and cut into pieces to obtain a positive electrode sheet with an area density of about 4 mg.
[0079] (2) NaClO4 (1 mol / L) was dissolved in a mixed solvent with a mass ratio of EC:PC of 1:1, and then 5% of the total volume mass of FEC was added as an additive.
[0080] (3) Assemble the positive and negative electrode sheets, the sodium metal sheet, and the glass fiber separator prepared in step 1 and add 100uL of the above-mentioned electrolyte. Then seal and let stand for 10 hours to obtain a sodium ion button half-cell.
[0081] The reversible capacity and cycle performance of the prepared battery were tested. The charge and discharge voltage atmosphere was set to 2.0-4.0V. The battery was first charged for 2 cycles at a current of 0.1C and then started to cycle at 1C. The results are shown in Table 1.
[0082] Table 1 Performance test table of sodium ion button batteries assembled in the embodiments and comparative examples
[0083]
[0084] It can be seen from the data in Table 1 that the cycle performance of each embodiment is excellent and the capacity retention rate is high; while the cycle performance of the comparative example is poor and the capacity retention rate is low. 0.4 Fe 0.2 Mn 0.2 The average contents of O2 and Fe are the same, while the trends of Fe content in secondary particles from the core to the surface are respectively decreasing, unchanged, and increasing, while the trends of Ni and Mn are consistent. The relative content of Fe on the surface of the material in Example 1 is the lowest, so its capacity retention rate for 100 cycles is 92.4%, which is significantly higher than the material in Comparative Example 1 whose secondary particles do not have differences in Fe content inside and outside (77.5%); at the same time, for the material with high Fe content outside and low Fe content in Comparative Example 2, its capacity retention rate is further reduced to 70.4. It can be seen that the concentration gradient change of Fe gradually decreasing from the core to the surface can significantly improve its cycle stability. In addition, the material with a core-shell structure in Comparative Example 3 has a 100-cycle capacity retention rate of only 80.6%, indicating that although the material also has a surface with low Ni and Fe content, its core and shell are heterogeneous structures, and the stability of this structure in long cycles is poor, proving that the material with a concentration gradient change has a longer cycle life.
[0085] The method for determining the amount of transition metal dissolution of the material after the battery cycle is as follows: disassemble the target battery in the glove box, then take out the positive electrode, put the diaphragm, counter electrode and battery shell into a small bottle and immerse it in DMC. After sealing the vial, take out the glove box and ultrasonicate for 30 minutes, then take out the diaphragm, counter electrode and battery shell from the vial, rinse with DMC, and combine the washing liquid into the original vial. Transfer the sample solution in the vial to a 100mL beaker, add 5mL of aqua regia (excessive) and stir the reaction until the solution is clear. Then, place the beaker on an electric furnace and slowly heat to evaporate all the solvents, then add a certain amount of 0.1M dilute nitric acid to the bottle, dissolve the residual substance to obtain a sample solution, and perform ICP determination on the sample solution. The results are shown in Table 2.
[0086] Table 2 Transition metal ion dissolution test results of materials in Examples and Comparative Examples after battery cycling
[0087]
[0088]
[0089] As can be seen from Table 2, the total amount of ion dissolution after the material cycle in each embodiment with a gradient change in Fe content is relatively similar (5.31 ppm in Example 1), while the total amount of transition metal ion dissolution in Comparative Examples 1 and 2, in which Fe inside and outside the material is uniform or has a reverse gradient change, is significantly increased (7.15 and 8.96 ppm). The increase in Fe surface content not only leads to an increase in Fe dissolution, but also causes an increase in Ni and Mn dissolution, proving that an increase in Fe can aggravate the irreversible phase change on the surface of the material during the cycle; therefore, on the premise of ensuring that the Fe content meets the charge balance requirements, constructing a concentration gradient change in the secondary particles of the material, and reducing its content in the surface layer can effectively improve the surface structure stability of the material during the cycle, thereby obtaining a better capacity retention rate.
[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a full concentration gradient layered oxide positive electrode material, characterized in that: Here are the steps: (1) adding nickel-poor iron solution B into a storage tank containing nickel-rich iron solution A at a speed u1, and mixing in real time in the storage tank to obtain solution C; at the same time, adding solution C into a reactor containing a mixed solution of a complexing agent and an antioxidant at a speed u2; The complexing agent solution and the alkali solution are simultaneously introduced into the reaction kettle to carry out a feeding reaction; (2) Inert gas is introduced during the reaction process, and the feeding of the complexing agent solution and the alkali solution is stopped after the solution C is completely fed; the stirring speed in the kettle is adjusted and constant temperature aging is performed, and the precursor is obtained after separation, washing and drying; (3) The precursor is mixed with sodium salt and then calcined to obtain a full concentration gradient layered oxide positive electrode material.
2. The method for preparing a full concentration gradient layered oxide positive electrode material according to claim 1, characterized in that: In the step (1), the mass ratio of the complexing agent to the antioxidant in the mixed solution of the complexing agent and the antioxidant is (1-3):(1-5), the concentration of the complexing agent in the mixed solution is 10-30 g / L; the concentration of the complexing agent solution is 80-130 g / L; and the concentration of the alkaline solution is 4-10 mol / L.
3. The method for preparing a full concentration gradient layered oxide positive electrode material according to claim 2, characterized in that: The complexing agent is any one of ammonia water, ammonium sulfate, ethylenediamine and ammonium citrate; the antioxidant is sodium ascorbate or ascorbic acid; and the alkaline solution is a mixture of one or more of sodium hydroxide and potassium hydroxide solutions.
4. The method for preparing a full concentration gradient layered oxide positive electrode material according to claim 2, characterized in that: The molar ratio of nickel, iron and manganese ions in the nickel-rich iron solution A is Ni:Fe:Mn=(0.40-0.60):(0.25-0.40):(0-0.25); the molar ratio of nickel, iron and manganese ions in the nickel-poor iron solution B is Ni:Fe:Mn=(0.00-0.30):(0.00-0.20):(0.60-1.00).
5. The method for preparing a full concentration gradient layered oxide positive electrode material according to claim 4, characterized in that: The u1=15-25 mL / h, u2=45-75 mL / h and u2=3 u1.
6. The method for preparing a full concentration gradient layered oxide positive electrode material according to claim 5, characterized in that: During the feeding reaction process, the temperature in the kettle is 45-60°C, the pH is 10.5-12.0, the stirring speed in the kettle is 600-1000 r / min; and the constant temperature aging time is 8-12h.
7. The method for preparing a full concentration gradient layered oxide positive electrode material according to claim 6, characterized in that: In the step (3), the molar ratio of the precursor to the sodium element in the sodium salt is 1:(1.01-1.05).
8. The method for preparing a full concentration gradient layered oxide positive electrode material according to claim 7, characterized in that: The calcination in step (3) refers to heating the temperature to 900-1000°C at a rate of 3°C / min and maintaining the temperature for 12-20 hours.
9. A full concentration gradient layered oxide positive electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: From the core to the surface of this material, the relative content of nickel and iron elements decreases continuously, while the relative content of manganese element increases continuously.
10. Use of the full concentration gradient layered oxide positive electrode material according to claim 9 in sodium ion batteries.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material with stable oxygen variable valence and preparation method of sodium-ion battery positive electrode material
CN115020676A
Coated sodium-based layered oxide composite material, preparation method thereof and sodium ion battery
CN116826014A
Sodium-ion battery layered oxide positive electrode material, preparation method thereof and sodium-ion battery
CN117276551A
Preparation method and application of full-concentration-gradient high-nickel ternary material
CN113060773A
Preparation method of full-concentration gradient positive electrode material precursor, full-concentration gradient positive electrode material and preparation method of full-concentration gradient positive electrode material
CN114291855A